Analysis of Five Years Data of Special Newborn Care Unit in a Rural Medical College: Scope for Improvement in Neonatal Mortality and Morbidity - Bidyut Kumar Khuntdar; Sumon Mondal; Umesh Mudi; Mahesh Prasad Mohanta (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Neonatal mortality is the most important contributor towards infant mortality. Special Newborn Care Units (SNCUs) are part of the facility based newborn care of National Health Mission (NHM) and cornerstones for reducing neonatal mortality. Aim: To study the mortality and morbidity data of a tertiary care SNCU of rural tribal Eastern India and find out the focus area for improvement. Materials and Methods: This was a retrospective observational study carried out on 19397 babies admitted in the SNCU of Midnapore Medical College, Midnapore, West Bengal, India, from February 2016 to January 2021. Data were collected from the SNCU admission register and computerised reporting data of SNCU. In this study, five years admission and mortality data of the SNCU was analysed. Results: There were 67729 live births during the period between February 2016 and January 2021, out of which 8627 were admitted to the SNCU (inborn). There were 1195 deaths among the inborn babies, thus the mortality rate was13.8%. The number of outborn babies admitted during the study period was 10770, out of which 1357 babies died, thus the mortality rate was 12.6%. There was significantly higher mortality among inborn babies than outborn babies (13.8% vs. 12.6%). The major causes of admissions in the SNCU were prematurity (n=10167, 52.5%), Low Birth Weight (LBW) (n=11519, 59.3%), jaundice (n=4692, 24.19%), Hypoxic Ischaemic Encephalopathy (HIE) (n=4278, 22%) and sepsis (n=2161, 11.14%). The main causes of mortality were HIE (n=766, 30%), and sepsis (n=709, 27.78%), followed by respiratory distress syndrome (n=162, 6.3%), congenital malformations (n=77, 3%), and meconium aspiration syndrome (n=37, 1.45%). Conclusion: Prematurity and LBW were the major causes of morbidity and mortality. Sepsis and HIE were the major direct causes of mortality. Hence to reduce neonatal morbidity and mortality focus should be on preventing the above causes.